Effectiveness of Incenerator-Based Practice in Improving Student’s Environmental Health Care Behavior - Anwaruddin Hisyam; Nurul Aini Binti Ismail; Rokhayati; Safirina Aulia Rahmi; Arif Rahman (Viva Medika, 2026)
The waste emergency in Yogyakarta, following the collapse of the centralized waste management system and the closure of the Final Disposal Site (FDS), has necessitated the implementation of decentralized and self-managed waste solutions within institutional settings. In this study, the effectiveness of integrating incinerator technology as a practice-based intervention to enhance Environmental Health Care Behavior (EHCB) among university students was investigated. A quantitative pre-experimental study employing a one-group pretest–posttest design was conducted using total sampling (n = 46). The intervention consisted of structured demonstrations and supervised hands-on operation of a campus mini-incinerator embedded within environmental health learning activities. EHCB scores were analyzed using a paired-sample t-test. A statistically significant increase was identified between the pre-intervention mean score (Mean = 45.60) and the post-intervention mean score (Mean = 52.80), with p < 0.001. An improvement of 15.79%, accompanied by a large effect size, was observed. These findings indicate that experiential engagement with environmental technology enhances self-efficacy and facilitates the transformation of knowledge into responsible waste management behavior. The results underscore the importance of technology-enhanced experiential learning as an institutional strategy for strengthening sustainable environmental health practices within decentralized waste management systems